Water Hyacinth Fiber and Glass Powder in Eco-Based GRC Ceiling Production - Zahra, Fathiya Haniffa; Bagas Danu Ega; Shifa Fauziyah; Anno Mahfuda (Rekayasa Sipil, 2026)
GRC (Glassfiber Reinforced Cement) ceiling panels are widely used in building construction in Indonesia due to their strength and durability. However, increasing demand highlights the need for more sustainable and cost-effective alternatives. This study investigates the substitution of conventional materials with environmentally friendly waste: glass powder as a partial replacement for cement, and water hyacinth fibers—commonly regarded as invasive weeds—as a substitute for fiberglass. An experimental approach was applied using variations in water hyacinth fiber content (0%, 15%, 30%, 45%) and glass powder content (0%, 5%, 10%, 12.5%). The optimal density was achieved with a mixture of 30% water hyacinth fiber and 10% glass powder, reaching 1.87 g/cm³, which is 0.06 g/cm³ higher than standard GRC panels. The lowest water absorption, at 12.4%, occurred with a combination of 15% fiber and 5% glass powder—0.9% lower than that of conventional panels. The highest flexural strength, 87.149 kgf/cm², was recorded with 30% water hyacinth fiber and 10% glass powder, exceeding that of standard GRC panels by 10.788 kgf/cm². Cost analysis revealed a significant reduction in production costs. The most cost-efficient composition—30% water hyacinth fiber and 10% glass powder—reduced manufacturing costs by Rp 9,049,248 compared to conventional GRC panels. This study highlights the potential of utilizing locally available waste materials to improve the mechanical properties of GRC ceiling panels while reducing both environmental impact and production costs. The findings offer a promising advancement toward sustainable building material innovation in Indonesia.